Comparative Evaluation of Different Numerical Pain Scales Used for Pain Estimation during Debonding of Orthodontic Brackets - Mohmed Isaqali Karobari; Ali A Assiry; Mubashir Baig Mirza; Fazlur Rahman Sayed; Sufiyan Shaik; Anand Marya; Adith Venugopal; Mohammad Khursheed Alam; Rithvitou Horn (Hindawi Limited, 2021)
Introduction. Patients experience various levels of discomfort during orthodontic treatment, i.e., after placement of separators, orthodontic implant placement, and archwire placement and during debonding. Various pain control methods have been developed to relive pain during debonding, i.e., finger pressure (FP), elastomeric wafer (EW), and stress relief (SR). Aim. To analyse various pain scales commonly used to determine the effect of different pain control methods during debonding of orthodontic brackets. Study Design. A comparative cross-sectional study performed on a sample of 60 patients (n = 60) including 14 males and 46 females who were ready for debonding and who were divided into three groups, i.e., finger pressure (FP), elastomeric wafer (EW), and stress relief (SR). Materials and Methods. A 100 mm Visual Analog Scale (VAS) was used to record the pain intensity for each tooth. Another scale known as Pain Catastrophizing Scale (PCS) was used to evaluate the patient's general attitude towards pain perception. The armamentarium and operator were kept same for all the patients. Statistical analysis used was the Kruskal-Wallis test, used for intergroup and intragroup comparison of pain scores. Results. Lowest total pain score was recorded in the FP group (P=0.043) on intergroup comparison, while on intragroup comparison, higher pain scores were recorded in lower anterior region (P=0.02) in all three groups. There was no significant difference between the pain scores reported by the male and female subjects. Conclusion. FP is an effective method of pain control. And teeth in the anterior region of lower and upper arches are more sensitive to pain. In terms of cognitive-affective constructs, although the VAS has been widely used in previous studies, the PCS has been detailed to show the most reliable association with physical discomfort and emotional distress.